Kepemilikan Keluarga, Leverage, dan Pengungkapan CSR terhadap Tax Avoidance dengan Kepemilikan Institusional Sebagai Variabel Pemoderasi - Sagina, Debby Mutiara; Leniwati, Driana; Haryanti, Agustin Dwi; Wicaksono, Agung Prasetyo Nugroho (Akuisisi : Jurnal Akuntansi, 2024)
This study aimed to analyze the effect of family ownership, leverage, and corporate social responsibility disclosure on tax avoidance with institutional ownership as a moderating variable. Determination of the number of samples using a purposive sampling method. The method used is a quantitative descriptive approach.  Data analysis was carried out using Smart PLS 3.2.9. The results of hypothesis testing show that family ownership and leverage affect tax avoidance, while corporate social responsibility does not affect tax avoidance. Then, the leverage value will increase tax avoidance in the company if the interest expense arising from the use of debt is included in the expense, which can reduce taxable income. Institutional ownership can strengthen the influence of family ownership, leverage, and corporate social responsibility on tax avoidance. This is because institutional ownership owns 98% of the company research sample. This means the proportion of share ownership from institutional parties is quite high